Analyzing transformation pathways to a sustainable European energy system—Internalization of health damage costs caused by air pollution. (November 2019) - Schmid, Dorothea; Korkmaz, Pinar; Blesl, Markus; Fahl, Ulrich; Friedrich, Rainer
Abstract: On its way to a low-carbon society, various transformation pathways for the European energy system are possible. Additionally, improving air quality may benefit from or influence climate change mitigation. In a comparative scenario analysis, interactions between decarbonization targets and air pollution control as well as their implications on the European energy system are studied. For this purpose, the European energy system model TIMES PanEU is linked with the impact assessment model EcoSense to internalize the health costs related to air pollution. Results indicate that ambitious GHG reduction targets are most influential with respect to system transformations. Internalizing health impacts leads to welfare savings by reducing air pollution while still achieving the given reduction targets with lower utilization of carbon capture and storage as well as biomass. Especially the latter may partially be contradictory to targets on the share of renewable energy sources. Hence, integrated policies tackling climate change and air pollution alike may foster the transition to a low-carbon society. To gain a better understanding of the interplay between reduction targets, the share of renewable energy sources, and air pollution control, further research studying sector- and country-specific impacts in more detail is still needed. Highlights: Energy system model TIMES PanEU is coupled with the impact assessment model EcoSense. GHG reduction targets are most influential driving energy system transformations. Considering cost of air pollution leads to less CCS deployment. RES targets fostering biomass may hinder air pollution control. An integrated view on climate change and air quality may foster a low-carbon society.